The Privilege of The Indonesia Investment Authority in Indonesia Omnibus Law on Job Creation - Putu Samawati; Shinta Paramita Sari (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2021)
Economic globalization has an impact on the dynamics of adjusting the legal rules established in Indonesia. One of them is the legal unification format called the Omnibus Law on Job Creation. The Omnibus Law on Job Creation collects laws related to development and investment. The new thing in this law is the formation of a new institution called the Sovereign Wealth Fund. Various privileges are given to an institution called the Indonesia Investment Authority (IIA), ranging from not being held accountable for a loss to being audited only by a public accountant. This article discusses how laws and regulations build the construction of the Sovereign Wealth Fund Indonesia. The main problem that was analyzed is how the position of the Sovereign Wealth Fund in the structure of the Indonesian state institutions, besides that, it also discusses the issue of the authority and responsibility of the Sovereign Wealth Fund as well as the privileges provided by laws and regulations. All of these issues be the scope of discussion that provides an overview of Indonesia's Sovereign Wealth Fund. The discussion was conducted using a normative juridical method through qualitative analysis using a statutory approach and legal philosophy approach. The inductive conclusion is expected to provide input in strengthening IIA construction so as not to get demands for discriminatory treatment by other state institutions, and the goal of being established by the IIA to accelerate national economic development can be realized.Keywords: Privilege, Indonesia Investment Authority, Omnibus Law on Job Creation, Sovereign Wealth Fund. Keistimewaan Indonesia Investment Authority Dalam Omnibus Law Cipta Kerja Indonesia Abstrak Globalisasi ekonomi berdampak pada dinamika penyesuaian aturan-aturan hukum yang ditetapkan di Indonesia. Salah satunya adalah format penyatuan hukum yang diberi nama Omnibus Law Cipta Kerja. Omnibus Cipta Kerja ini menghimpun undang-undang yang berkaitan dengan pembangunan dan investasi. Hal baru yang diatur dalam undang-undang ini adalah pembentukan lembaga baru yang diberi nama Soverign Wealth Fund. Berbagai keistimewaan diberikan kepada lembaga yang diberi nama Indonesia Investment Authority (IIA), mulai dari tidak dapat dimintakan pertanggung jawaban apabila mengalami kerugian hingga hanya dapat diaudit oleh akuntan publik. Artikel ini membahas mengenai bagaimana peraturan perundang-undangan membangun konstruksi Soverign Wealth Fund Indonesia. Permasalahan utama yang dianalisis adalah bagaimana kedudukan Soverign Wealth Fund dalam struktur lembaga negara Indonesia, selain itu juga dibahas mengenai persoalan kewenangan dan tanggung jawab Soverign Wealth Fund serta keistimewaan-keistimewaan yang diberikan oleh peraturan perundang-undangan. Kesemuaan permasalahan ini menjadi ruang lingkup pembahasan yang akan memberikan gambaran mengenai Soverign Wealth Fund Indonesia. Pembahasan dilakukan dengan metode yuridis normatif melalui analisis secara kualitatif yang menggunakan pendekatan perundang-undangan dan pendekatan filsafat hukum. Kesimpulan secara induktif diharapkan dapat memberikan masukan dalam menguatkan konstruksi IIA agar tidak mendapatkan tuntutan perlakuan diskriminasi oleh lembaga negara lain, dan tujuan didirikan IIA untuk percepatan pembangunan perekonomian nasional dapat terealisasi.Kata Kunci: Keiistimewaan, Indonesian Investment Authority, Omnibu Law Cipta Kerja, Lembaga Pengelola Investasi Привилегии инвестиционного управления Индонезии по Закону Омнибуса о создании рабочих мест в ИндонезииАннотацияЭкономическая глобализация влияет на динамику регулировки правовых норм, установленных в Индонезии. Одна из них - это юридический формат унификации, который называется Законом Омнибуса о создании рабочих мест. Закон Омнибуса о создании рабочих мест включает в себя законы, связанные с развитием и инвестициями. Новым в этом законе является создание нового учреждения под названием Фонд Национального Благосостояния (Sovereign Wealth Fund). Учреждению, называемому Инвестиционным Управлением Индонезии (IIA), предоставляются различные привилегии, от отсутствия ответственности за убытки до проверки только государственным аудитором. В этой статье обсуждается, как законы и нормативные акты строят структуру Фонда Суверенного Благосостояния Индонезии. Основная проблема, которая была проанализирована, заключается в том, какое положение у Фонда Суверенного Благосостояния в структуре государственных учреждений Индонезии, помимо этого, также обсуждается вопрос о полномочиях и ответственности Фонда Суверенного Благосостояния, а также о привилегиях, обеспеченных законами и регулированиями. Все эти вопросы являются предметом обсуждения, который дает обзор Фонда Суверенного Благосостояния Индонезии. Обсуждение проводилось с использованием нормативно- правового метода посредством качественного анализа с использованием статутного подхода и философско-правового подхода. Предполагается, что индуктивный вывод внесет вклад в укрепление построения IIA, чтобы не получить требований о дискриминационном обращении со стороны других государственных учреждений, и цель, поставленная IIA для ускорения национального экономического развития, может быть реализована.Ключевые Слова: Привилегия, Инвестиционное Управление Индонезии, Закон Омнибуса о создании рабочих мест, Фонд национального благосостояния